2022
DOI: 10.1093/gerona/glac226
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Plasma Levels and Changes on Physical and Cognitive Capacities in Community-Dwelling Older Adults

Abstract: Background Periostin, involved in extracellular matrix development and support, has been shown to be elevated in senescent tissues and fibrotic states, transversal signatures of aging. We aimed to explore associations between plasma periostin and physical and cognitive capacity evolution among older adults. Our hypothesis was that higher levels of plasma periostin will be associated with worse physical and mental capacities along time. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Additionally, we found that increased physical activity in elderly individuals restored hPOSTN-concentrations to levels found in young adults (Figure 7A). As previous studies had reported elevated levels of circulating Periostin due to certain pathologies 65 , we also assessed serum hPOSTN in a group of healthy older individuals compared to age-matched individuals living in an acute geriatric hospital setting. No differences were found, indicating that circulating hPOSTN is not applicable as a generalized marker of impaired health status (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found that increased physical activity in elderly individuals restored hPOSTN-concentrations to levels found in young adults (Figure 7A). As previous studies had reported elevated levels of circulating Periostin due to certain pathologies 65 , we also assessed serum hPOSTN in a group of healthy older individuals compared to age-matched individuals living in an acute geriatric hospital setting. No differences were found, indicating that circulating hPOSTN is not applicable as a generalized marker of impaired health status (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it stands to reason that loss of circulating Periostin may also inform on the progression of muscle degeneration as a result of age-related sarcopenia. It should be noted that increased levels of Periostin have also been proposed as a biomarker of disease progression in older adults, including cognitive decline 65 , suggesting that associations such as those found in our cohorts need to be evaluated in more detail. In conclusion, our study presents a novel role of FAP-based synchronization of the muscle stem cell niche, which links impaired regeneration to age-related niche deterioration and fatty degeneration of skeletal muscle.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the administration of ACE inhibitors in hypertensive patients diagnosed with AD has been correlated with increased handgrip strength (HGS), preservation of physical capacity, and the prevention of neuromuscular junction (NMJ) degradation [ 32 ]. In a recent study, researchers observed a noteworthy relationship between elevated plasma POSTN levels and the progressive decline in physical and cognitive capacities among older adults [ 33 ]. We have already produced a bioanalytical platform that can measure four biomarkers with tens of microliters of peripheral blood, the so-called Quantamatrix’s multiplexed diagnostics platform (QPLEX™; Quantamatrix Inc., Seoul, Republic of Korea) Alz plus assay kit.…”
Section: Introductionmentioning
confidence: 99%